Extremal Optimization : Fundamentals, Algorithms, and Applications /: Fundamentals, Algorithms, and Applications. (2016) - Lu, Yong-Zai; Chen, Yu-Wang; Chen, Min-Rong; Chen, Peng; Zeng, Guo-Qiang
No abstract available